Case Report: Iptacopan in a paroxysmal nocturnal hemoglobinuria patient with severe renal insufficiency - Ting Wu; Xiaoqin Wang (Frontiers in Medicine)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare disorder characterized by complement-mediated hemolysis, thrombosis, and bone marrow failure. Iptacopan, an oral factor B inhibitor, has demonstrated efficacy in managing PNH but has not been studied in patients with severe renal insufficiency. We report a case of a PNH patient with end-stage renal disease who required renal replacement therapy and had a peritoneal dialysis catheter placed during treatment. After switching from eculizumab to iptacopan, the patient achieved transfusion independence, sustained hematologic improvement, and resolution of both intravascular and extravascular hemolysis. Iptacopan was well tolerated, with only mild adverse effects and no breakthrough hemolysis or infections. This case highlights the potential of iptacopan as a therapeutic option in PNH patients with severe renal impairment requiring dialysis.